Correlation of features on OCT with visual acuity and Gass lesion type in Best vitelliform macular dystrophy. Issue 1 (7th December 2021) - Coussa, Razek G; Fortenbach, Christopher R; Critser, D Brice; Collins, Malia M; Tucker, Budd A; Mullins, Robert F; Sohn, Elliott H; Stone, Edwin M; Han, Ian C
Abstract : Objective: To correlate structural features seen on optical coherence tomography (OCT) with best-corrected visual acuity (BCVA) and Gass lesion type in patients with Best vitelliform macular dystrophy (BVMD). Methods and analysis: This is a retrospective case series of consecutive patients with molecularly confirmed BEST1- associated BVMD. OCT scans were reviewed for lesion status and presence of subretinal pillar, focal choroidal excavation (FCE), intraretinal fluid or atrophy. Available OCT angiography images were used to evaluate for the presence of choroidal neovascularisation (CNV). These features were then correlated with BCVA and Gass lesion type. Results: 95 eyes from 48 patients (mean age 38.9 years, range 4–87) were included. The presence of a pillar (24.2%), FCE (20.0%) and atrophy (7.4%) were associated with poor BCVA (p<0.05). Gass lesion type 1 eyes were correlated with good BCVA (LogMAR <0.4) whereas type 5 eyes had poor BCVA (LogMAR >0.4). Among 65 eyes with longitudinal data (mean follow-up 5.1 years), 7 eyes (10.8%) reverted from higher to lower Gass lesion type; of these, 4 eyes (57.1%) had CNV responsive to intravitreal anti-vascular endothelial growth factor treatment. Conclusion: OCT-based structural features are readily identifiable in patients with BVMD and have prognostic importance due to their correlation with BCVA.